Analisa Safety Factor Sheet Pile Pada PLTMG Pontianak Peaker Dengan Aplikasi Geo5 - Muhammad Amar Sajali; Rahmah Dara Lufira; Suwanto Marsudi; Aufa Hanan A (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2019)
In the past decade, the development of land retaining construction is growing rapidly as optimization of available land use. The purpose of this study is to hold the soil in order to avoid landslide due to the structural load other than the use of available space. The results of the sheet pile analysis at Pontianak Peaker PLTMG found that the SF number in the condition without earthquake (safe condition) is 2.00 and the number of SF in earthquake conditions is 1.40. Based on the results of sheet pile analysis at S-02 and S-03 points in conditions without earthquakes, low tide-without earthquakes, floods-without earthquakes, normal-earthquakes, receding earthquakes, and earthquake floods with earthquakes returning 500 years in analysis the structure and analysis of slope stability are said to be "safe" because the conditions without earthquakes SF values greater than 2.00 and earthquake conditions SF values greater than 1.40.